THE RELATIONSHIP OF TEACHER TEACHING SKILLS AND LEARNING INTERESTS OF PHYSICS STUDENTS OF SENIOR HIGH SCHOOL - Aldila, Febri Tia; Rini, Endah Febri Setiya; Octavia, Sri Wina; Khaidah, Hikma Nur; Sinaga, Feliza Paramitha; Septiani, Neni (EduFisika: Jurnal Pendidikan Fisika, 2023)
This study aims to determine the relationship between teacher teaching skills and students' interest in learning physics at senior high school 2 Batanghari. The method used is the quantitative method, the type of research used is correlational, the sample in this study is teachers and students of senior high school 2 Batanghari, the instrument used is a questionnaire, and the data analysis technique is descriptive and inferential statistics. The results of this study indicate that the teaching skills of physics teachers and the learning interests of physics students have a significant relationship.